Da retórica ao retweet : os elementos persuasivos nos discursos do ex-governador Marcelo Déda, compartilhados no Twiiter - Rodrigues, Carolina Bueno (2016)
This paper proposes to investigate the persuasive elements present in the speeches of Sergipe former governor Marcelo Déda, published in his personal Twitter account. Marcelo Déda was one of the main representatives not only of the Northeast of Brazil but also the entire country - between 2010 and 2013 - in the use of online social networks for political and governmental purposes. Due to the need to examine instances of production and circulation of these discourses, according to the argumentative strategies used by Déda, the aim of this study is grounded in textual analysis method Discourse proposed by Galiazzi and Moraes (2007), which uses the analysis speech at the production stage and the content analysis, the circulation stage of tweets. For the particularities of the object, it was also carried out a biographical study of the former governor, according to the guidelines suggested by Gobbi ( DUARTE ed., 2010), to contextualize its discursive profile. In addition to this study, it is presented here all the material collected and the guiding concepts that supported this research. The results of the analyzes show that the policy-governmental communication appropriates various techniques and rhetorical elements of language, also common in advertising, and it is becoming more appropriate to the new reality of convergence of multiple information flows of social media on search of the collective ownership of ideas.